2010
DOI: 10.1007/s10570-010-9414-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of microfibril contraction and anisotropic dimensional changes for cells in wood treated with aqueous NaOH solution

Abstract: Anisotropic swelling of wood samples was observed upon treatment with an aqueous NaOH solution with 0-0.20 fraction concentrations. At NaOH concentrations less than 0.10, the swelling occurred only along the tangential axis (T) and not along the radial (R) or longitudinal (L) axes. At greater NaOH levels, the swelling was even more pronounced along T with shrinkage along the other axes. These anisotropic changes along R and L were closely related to the crystallinity of microfibrils in the wood cell wall and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…Previous studies support this possibility, and reported that the strong alkali treatment (mercerization) caused the longitudinal contraction of wood samples (Ishikura & Nakano, 2007;Nakano, Sugiyama, & Norimoto, 2000) and the in-plane contraction of cellulose samples, including a wet sheet of bacterial cellulose (Shibazaki et al, 1997) and a dry sheet of microfibrillated cellulose (Nakagaito & Yano, 2008). As an explanation for these behaviors, Nakano et al proposed that the contraction is related to the entropy elastic force of cellulose microfibrils (Nakano, 2010;Nakano et al, 2000). Because the cellulose nanofiber isolated in this study corresponds to the cellulose microfibril aggregates (or bundles) in wood cell walls (Donaldson, 2007;Fahlén & Salmén, 2005;Tarashima et al, 2010), their proposal may be applied to our example.…”
Section: Fe-sem Observationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies support this possibility, and reported that the strong alkali treatment (mercerization) caused the longitudinal contraction of wood samples (Ishikura & Nakano, 2007;Nakano, Sugiyama, & Norimoto, 2000) and the in-plane contraction of cellulose samples, including a wet sheet of bacterial cellulose (Shibazaki et al, 1997) and a dry sheet of microfibrillated cellulose (Nakagaito & Yano, 2008). As an explanation for these behaviors, Nakano et al proposed that the contraction is related to the entropy elastic force of cellulose microfibrils (Nakano, 2010;Nakano et al, 2000). Because the cellulose nanofiber isolated in this study corresponds to the cellulose microfibril aggregates (or bundles) in wood cell walls (Donaldson, 2007;Fahlén & Salmén, 2005;Tarashima et al, 2010), their proposal may be applied to our example.…”
Section: Fe-sem Observationsmentioning
confidence: 95%
“…The procedure basically followed the method we used in previous studies (Abe et al, 2007;Abe & Yano, 2009, 2010. Wood powder was purified by a series of chemical treatments as follows.…”
Section: Purification and Isolation Of Cellulose Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase reactivity and swell lignocellulosic materials before modifi cation, the material was treated with alkaline solution. Alkaline treatments contracts microfi brils in the cell wall and changes the dimension (Nakano, 2010). The mechanism of microfibril contraction and anisotropic dimensional changes of cells in wood are treated with aqueous NaOH solution.…”
Section: Rezultati I Raspravamentioning
confidence: 99%
“…In contrast to that, LOI increased with the NaOH, KOH and LiOH concentration. It is probably due to the transition between cellulose polymorph and the effect of alkali ion (Nakano, 2010;Borysiak and Doczekalska, 2005). The lowest TCI and LOI values were observed on untreated materials, which may indicate that the amorphous region is higher in untreated materials than after alkali treatment when mercerization takes place.…”
Section: Rezultati I Raspravamentioning
confidence: 99%